ANALYZING INDONESIA PRIVATE AND STATE-OWNED TELECOMMUNICATION COMPANIES - Prakoso , Prabukusumo
The development of telecommunication industry has played as a vital global infrastructure to define the information flows. Globalization has also one of the variables that excel the industry development process. For Indonesia, the development of the telecommunication itself derived from the government initiative by establishing a privately owned company that provides mail service and telegraph. This communication service has a tremendous effort for the distribution of the information in the Netherlands colony, considering the geographical challenges of Indonesia. Then at 1961, this status has changed to be Perusahaan Negara Pos dan Telekomunikasi (State-owned Post and Telecommunication Company) and by the year 1986 the company has split in to two which is the Perusahaan Negara Pos dan Giro ( The state-owned Post and Giro Company) and Perusahaan Negara Telekomunikasi ( The State-owned Telecommunication Company. We put forward a theory of the optimal capital structure of the firm based on Modigliani and Miller (Levine ,1958:23) hypothesis that the value of a firm is unaffected by how that firm is financed in an efficient market. This study investigates the capital structure pattern of the Telecommunication companies which is listed in the Jakarta Stock Exchange and determines the factors that influence the capital structure behavior over different type of financing in Indonesia. The impact of economic condition and industrial on long-term, short- term, total debt ratios was studied. The findings shows that state owned company has a tendency in adjusting their debt ratio in responding to the long run of monopolization in this industries. Besides, the debt ratio was found to be industry specific and it is best used in analyzing the related companies in the same industry. Result from the independent t-test samples shows that the ratio of debt ratio, debt to equity ratio, return on assets, return on equity, and current assets are the variables that have the lower ratio on the state-owned company than the private-owned company. All the determinants proved to agree with the Modigliani theories and previous findings in the Shumi Akhtars journals in developed this final project. The assumptions also indicate time effect and the determinants behave differently under different economic condition will remain constant, yet the result will illustrate the ratio pattern which is treated from the financial ratio in the financial statements of each companies, particularly in dividing the state and private-owned company in Indonesia. From seeing the company profile that operates in Indonesia, it indicates that the telecommunication industry is competitive both in technology and its service. So it is dependable to the company in answering the challenge from the global telecommunication users and capital structure is one of the key to determine the performance on each company and to analyze the significant patterns which the state and private owned company responds to the dynamics of telecommunication industry.